2015
DOI: 10.1016/s1473-3099(15)00154-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dose on the safety and immunogenicity of the VSV Ebola candidate vaccine: a randomised double-blind, placebo-controlled phase 1/2 trial

Abstract: Wellcome Trust through WHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
282
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(317 citation statements)
references
References 31 publications
15
282
4
6
Order By: Relevance
“…After preliminary data indicated tolerability and immunogenicity of low vaccine doses in other studies, the study was resumed in Geneva, but at a lower dose of 3 × 10 5 pfu, comparing outcomes to those of vaccinees who had received the higher doses before the study was put on hold. 26 Patterns of detectable viremia were comparable with other studies that investigated the rVSVΔG-ZEBOV-GP vaccine; viremia was transient, peaking by day 3 and no longer evident on day 7. 16,24,26 Glycoprotein-binding serum antibodies were detectable in all vaccinated individuals, irrespective of vaccine dose.…”
Section: Discussionsupporting
confidence: 81%
“…After preliminary data indicated tolerability and immunogenicity of low vaccine doses in other studies, the study was resumed in Geneva, but at a lower dose of 3 × 10 5 pfu, comparing outcomes to those of vaccinees who had received the higher doses before the study was put on hold. 26 Patterns of detectable viremia were comparable with other studies that investigated the rVSVΔG-ZEBOV-GP vaccine; viremia was transient, peaking by day 3 and no longer evident on day 7. 16,24,26 Glycoprotein-binding serum antibodies were detectable in all vaccinated individuals, irrespective of vaccine dose.…”
Section: Discussionsupporting
confidence: 81%
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Therefore, another 56 participants were recruited to continue this trial, with 43 of them were randomly assigned to receive lower dose rVSV-EBOV of 3 £ 10 5 vp or placebo and 13 only received open-label rVSV-EBOV at 3 £ 10 5 vp (NCT02287480). 54 The results showed that the dose reduction to 3 £ 10 5 vp could decreased the occurrence of viremia, but 13 low-dose vaccinees (25%) still occurred arthralgia after immunization. Additionally, another 2 participants reported purpura on the lower legs and the counts of lymphocyte, neutrophil, and platelet decreased significantly at day 1-3 post-vaccination.…”
Section: Rvsv-ebovmentioning
confidence: 93%